Construction Claim Types and Causes for a Large-Scale Hydropower Project in Bhutan - Hadikusumo, Bonaventura H.W.; Tobgay, Sonam (Penerbit Universiti Sains Malaysia, 2015)
Hydropower construction projects are complex and uncertain, have long gestational periods and involve several parties. Furthermore, they require the integration of different components (Civil, Mechanical and Electrical) to work together as a single unit. These projects require highly specialised designs, detailed plans and specifications, high-risk construction methods, effective management, skilful supervision and close coordination. Thus, claims are common in such projects. These claims are undesirable because they require significant time and resources to resolve and cause adversarial relationships among the parties involved. Therefore, it is in the common interest of all involved parties to prevent, minimise, or resolve claims as amicably as possible. Identifying common claim types and their causes is essential in devising techniques to minimise and avoid them in future projects. This report details a case study performed on a large-scale hydropower project in Bhutan. The findings of this case study indicate that differing site conditions are the major contributor of impact and change claims and 95% of total claims can be settled by negotiation, whereas 5% of claims can be settled by arbitration.